New insights into venture capitalists' activity: IPO and time-to-exit forecast as antecedents of their post-investment involvement - Gerasymenko, Violetta; Arthurs, Jonathan D. (Journal of Business Venturing, 2014)
We examine how VCFs' forecast of an IPO exit affects their breadth of advising and the likelihood of founder–CEO replacement shortly after they invest in a new venture. Moreover, we examine how the expected time-to-exit moderates these relationships. Our findings show that the likelihood of founder–CEO replacement upon receiving venture capital funding is significantly greater if a VCF perceives this company as a potential IPO as opposed to a trade sale, and this likelihood increases if the forecasted time-to-exit is short. We also illustrate how the breadth of advice varies as a function of the forecasted IPO and time-to-exit.